TetrazineBox: A Structurally Transformative Toolbox - Guo, Qing-Hui; Zhou, Jiawang; Mao, Haochuan; Qiu, Yunyan; Nguyen, Minh T; Feng, Yuanning; Liang, Jiaqi; Shen, Dengke; Li, Penghao; Liu, Zhichang; Wasielewski, Michael R; Stoddart, J. Fraser (Journal of the American Chemical Society, 2020)
Synthetic macrocycles capable of undergoing allosteric regulation by responding to versatile external stimuli are the subject of increasing attention in supramolecular science. Herein, we report a structurally transformative tetracationic cyclophane containing two 3,6-bis(4-pyridyl)-l,2,4,5-tetrazine (4-bptz) units, which are linked together by two p-xylylene bridges. The cyclophane, which possesses modular redox states and structural post-modifications, can undergo two reversibly consecutive two-electron reductions, affording first its bisradical dicationic counterpart, and then subsequently the fully reduced species. Furthermore, one single-parent cyclophane can afford effectively three other new analogs through box-to-box cascade transformations, taking advantage of either reductions or an inverse electron-demand Diels–Alder (IEDDA) reaction. While all four new tetracationic cyclophanes adopt rigid and symmetric box-like conformations, their geometries in relation to size, shape, electronic properties, and binding affinities toward polycyclic aromatic hydrocarbons can be readily regulated. This structurally transformative tetracationic cyclophane performs a variety of new tasks as a result of structural post-modifications, thus serving as a toolbox for probing the radical properties and generating rapidly a range of structurally diverse cyclophanes by efficient divergent syntheses. This research lays a solid foundation for the introduction of the structurally transformative tetracationic cyclophane into the realm of mechanically interlocked molecules and will provide a toolbox to construct and operate intelligent molecular machines.